PENGARUH PENERAPAN METODE BERMAIN DENGAN MENGGUNAKAN STIK TERHADAP KEMAMPUAN BERHITUNG PERMULAAN PADA ANAK USIA 5-6 TAHUN DI PAUD IBU TELADAN KECAMATAN TAMPAN PEKANBARU - Rita Setiyowati; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of using a stick to play the beginning of the numeracy skills of children aged 5-6 years in early childhood Ibu Teladan Sidomulyo West Village District Tampan Pekanbaru .. The population in this study were children aged 5-6 years were 17 children who consists of 8 girls 9 boys laki.Sampel this study using saturated sampling technique, which took the total sample of the population that is 17 children. Data collection techniques used were documentation and observation. Data were analyzed using t-test analysis. Coefficient can be seen pretest and posttest data correlation of r = 0852 and p = 0.000. Because the value of P <0.05 (0.000 <0.05) in the Ha received a significant difference in the ability of the child after the beginning of the counting method using a stick to play with at the age of 5-6 years. Statistical test obtained with t = -18.00 test two parties mean the absolute price, so the value (-) can not be used (Sugiyono, 2010). Then the price of the t (18:00), df = 16 and standard error of 5% = 2,120. Can be seen the price of t is greater than t table at the level of misunderstanding of 5% (18:00> 2.120). Thus Ho rejected and Ha accepted. While the contribution method using a stick playing against numeracy beginning amounted to 72.7% is determined by other factors remaining 27.3% were not examined in this study.Keywords: play using sticks, numeracy starters.